2002
DOI: 10.1128/mcb.22.13.4803-4814.2002
|View full text |Cite
|
Sign up to set email alerts
|

Myogenic Akt Signaling Regulates Blood Vessel Recruitment during Myofiber Growth

Abstract: Blood vessel recruitment is an important feature of normal tissue growth. Here, we examined the role of Akt signaling in coordinating angiogenesis with skeletal muscle hypertrophy. Hypertrophy of C2C12 myotubes in response to insulin-like growth factor 1 or insulin and dexamethasone resulted in a marked increase in the secretion of vascular endothelial growth factor (VEGF). Myofiber hypertrophy and hypertrophy-associated VEGF synthesis were specifically inhibited by the transduction of a dominant-negative muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
134
2
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(151 citation statements)
references
References 69 publications
12
134
2
1
Order By: Relevance
“…Transduction with dominant-negative Akt also inhibited capillary formation in Matrigel plugs implanted in mice. While a number of studies have shown that constitutive activation of Akt signaling is sufficient to promote angiogenesis in vivo (37,56,57), the data presented here provide the first direct evidence showing that Akt signaling is essential for neovascularization in an animal model.…”
Section: Ampk Regulates Capillary Formation In Matrigel Plugs In Vivo-mentioning
confidence: 71%
See 1 more Smart Citation
“…Transduction with dominant-negative Akt also inhibited capillary formation in Matrigel plugs implanted in mice. While a number of studies have shown that constitutive activation of Akt signaling is sufficient to promote angiogenesis in vivo (37,56,57), the data presented here provide the first direct evidence showing that Akt signaling is essential for neovascularization in an animal model.…”
Section: Ampk Regulates Capillary Formation In Matrigel Plugs In Vivo-mentioning
confidence: 71%
“…Stimuli that may activate endothelial AMPK in vivo include decreases in oxygen tension that are associated with tumor growth or occlusive vessel diseases (29,59). In contrast, angiogenesis associated with normal tissue growth and organ enlargement during development can be subject to regulatory controls that function independently of tissue oxygen gradients (56,60). Collectively, these data suggest endothelial AMPK signaling may be an essential feature of the angiogenic response to ischemic stress, while having minimal effects on angiogenic endothelial cell responses during FIG.…”
Section: Ampk Regulates Capillary Formation In Matrigel Plugs In Vivo-mentioning
confidence: 83%
“…It is also recognized that skeletal muscle hypertrophy is coupled to angiogenesis, through molecular mechanisms that are independent of tissue hypoxia (6). VEGF, a strong stimulator of angiogenesis, is up-regulated during myofiber hypertrophy by myogenic Akt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of constitutively active Akt1 in skeletal muscle stimulates muscle hypertrophy both in vitro and in vivo (6 -9). Adenovirus-mediated transduction of constitutively active Akt1 also promotes the induction of the vascular endothelial growth factor (VEGF), 3 and this is accompanied by an increase in limb perfusion and capillary density in muscles where Akt1 is overexpressed (6). Constitutive activation of Akt1 in the heart also promotes myocardial angiogenesis, which is partly mediated by the induction of VEGF (10,11).…”
mentioning
confidence: 99%
“…Therefore, PI3K activity is necessary for IGF-1 to induce hypertrophy, and its activation is sufficient to induce hypertrophy. Expression of an activated form of Akt1 in skeletal muscle cells is sufficient to induce hypertrophy [33,36,37]. Downregulation of the Akt pathway has been observed in skeletal muscle atrophy [20].…”
Section: Heart Failure and Angiotensin IImentioning
confidence: 99%